Update on cerebrotendinous xanthomatosis. Issue 2 (April 2021) - DeBarber, Andrea E.; Duell, P. Barton
Abstract : Purpose of review: Cerebrotendinous xanthomatosis (CTX) is a rare genetic lipid storage disorder with highly pleomorphic clinical phenotype. Complications of this disease can be devastating and may include severe cognitive impairment and dementia in later stages. Disease progression can be prevented or stabilized by bile acid replacement therapy, although a subset of patients with advanced disease continue to deteriorate despite therapy. Recent findings: Delayed diagnosis of CTX continues to impede effective treatment. A clinical diagnostic algorithm for CTX was developed that can decrease the age of diagnosis of CTX. The strategy of screening children with bilateral juvenile cataracts for CTX also improved diagnosis, as this group had a 500-fold higher-rate of CTX than the general population. Improved diagnosis of CTX is critical, as patients treated early in the course of the disease have significantly better outcomes compared with those treated later. More sensitive and specific biochemical testing for CTX has been developed that is potentially more informative than blood cholestanol to assess treatment efficacy and medication compliance in CTX. Summary: Because we are recognizing more severe presentations of CTX in infants and children, and delayed diagnosis and treatment worsens the prognosis, CTX is an excellent candidate disorder for newborn screening using recently reported methods for newborn dried bloodspot analysis.